The utilization of social media as a marketing communication strategy for msme products in joho village, sukoharjo - Majid, Nur Riyadh; Santoso, Budi (Jurnal Mantik, 2024)
The majority of Micro, Small and Medium Enterprises (MSMEs) adopt social media platforms to communicate with their potential customers. The adoption of social media provides benefits for MSME managers that positively influence MSME performance. This research aims to determine the use of social media by MSMEs as a product marketing communication medium in Joho Village, Sukoharjo. In compiling this research, the researcher used a qualitative approach. The number of MSMEs that use social media to market products is 7 MSMEs from Joho Village. The types of MSMEs marketed are food, clothing, home equipment and women's accessories. The data sources used are primary data and secondary data. Data collection techniques are interviews and observation. The data analysis technique used in this research uses the Miles and Huberman model analysis method, namely data reduction, data presentation and drawing conclusions. The research results show that MSMEs in this study have used social media in their sales communication process. The most widely used social media is Facebook. The benefit of using social media for MSMEs is that it is an effective sales tool, it can increase sales volume by more than 100% if you always update information every day. This research also shows that the benefit most felt by MSME owners/managers in this research is that social media is very useful in: 1) facilitating effective communication between MSME managers, consumers and suppliers. 2) improve marketing and expand market share. 3) help increase the knowledge of SME managers and assist business decisions